Modeling radiation on Mars for solar particle events and galactic cosmic rays - Pfeifer, Michael Paul (Kansas State University, 2019)
Using the PHITS code system, Monte Carlo simulations of solar particle events (SPEs) and galactic cosmic rays (GCRs) were performed. The SPE model uses tally data to form kernel response functions that determine twelve different particle fluences when folded with measured solar spectra. A database of 577 solar events was analyzed to determine the probability and intensity of a large-scale event. As a shielding benchmark, the largest recorded SPE of October 19, 1989, was considered for absorbed dose and effective dose estimates. Since solar energetic particles have a high flux in the low energy domain, surface altitude makes a large difference in the dose received. To capture these effects, 11 locations on the Martian surface were simulated with special focus on the Hellas Planitia, Datum, and Olympus Mons. Simulation showed that the October 1989 SPE would have delivered an effective dose of 153mSv at the Hellas Planitia, 230mSv at the Datum, and up to 1Sv at Olympus Mons. It was determined that unshielded dose rates at high altitudes could put astronauts in jeopardy of reaching their lifetime effective dose limits, 30d organ absorbed dose limits, and could possibly cause acute radiation sickness. To minimize these risks, subterranean shelters using regolith as a passive shield were investigated. It was found that 25cm of Martian regolith is enough shielding to reduce proton absorbed dose rates by more than 75% bringing absorbed dose and effective dose to tolerable levels. A second model exploring dose rates for GCRs was also created to provide the full picture of the Mars radiation environment. The GCR source term was based on measured particle data from March 1, 2018, to July 1, 2018, which included particles ranging from protons to fully-stripped nickel ions. The geometry consisted of concentric spheres of true Mars size with density discretizations following atmospheric profiles defined by the NASA Glenn Research Center. A surface tally and volumetric tally were positioned at a column depth of 20gcm⁻², which is the average column depth measured by the Curiosity rover in the March to July 2018 time frame. An averaged flux density was tallied and converted to dose using coefficients defined in ICRP Publication 123 “Assessment of Radiation Exposure of Astronauts in Space”. It was found that GCRs are estimated to deliver 215.8µGy of absorbed dose per day. The effective dose was calculated to be 491µSv per day. For validation of these results, a surface crossing tally that estimated the particle flux within 30◦ from the zenith was compared to Mars Science Laboratory Radiation Assessment Detector (MSLRAD) data. It was found that the radiation flux for light ions had relatively good agreement with measured data. The integral particle fluxes were also shown to agree with measured data for protons and nuclei larger than boron.
Keywords: Space; Mars; Radiation; Transport